Synthesis of 2-acetyl-5,8-dihydro-1,4-dihydroxy-3-methyl naphthalene: a product from the isomerisation of Diels-Alder adducts of both 5-methyl- and 6-methyl-2-acetyl-1,4-benzoquinone with 1,3-butadiene - Ahmad, Faujan; Bruce, J. Malcolm (Taylor & Francis, 1996)
2-Acetyl-5,8-dihydro-1,4-dihydroxy-3-methyl-naphthalene was synthesised via Diels-Alder addition of 2-acetyl-3-methyl-1,4-benzoquinone to buta-1,3-diene followed by enolisation. It was identical with material obtained by pyridine-induced acetyl migration from the 1,3-butadiene adducts of both 3- and 6-methyl-2-acetyl-1,4-benzoquinone.